Anodic performance of black phosphorus in magnesium-ion batteries: the significance of Mg–P bond-synergy. Issue 54 (14th June 2016) - Banerjee, Swastika; Pati, Swapan K.
Abstract : Mg-ion storage within a covalent P-anode optimizes the anodic voltage and reduces the Mg-diffusion barrier, thereby can overcome the bottleneck in Mg-battery technology. Abstract : By means of first-principles analysis, we have shown that black phosphorus shows promise as a low potential and high capacity anode in Mg-ion batteries. The fact that deserves the most attention is synergistic interaction between Mg-ions and the covalent P-host that reduces the Mg-diffusion barrier and optimizes the anodic voltage, thereby can overcome the bottleneck in Mg-battery machinery.